Analisis Kinerja Routing Protocol Ad-hoc On Demand Multipath Distance Vector (AOMDV) Menggunakan Pergerakan Gauss-Markov Pada Mobile Ad-hoc Network (MANET) - Eko Aditya Ramadianto; Rakhmadhany Primananda; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Mobile Ad-hoc Network (MANET) is a topology that consist of several wireless nodes which can configure dynamically without using fix existing network infrastructure. Nodes in MANET can move freely and between nodes are connected through wireless networks. Due to the dynamic topology, an appropriate routing protocol is needed in determining the routing path between nodes in MANET topology. Ad-hoc On Demand Multipath Distance Vector (AOMDV) is a multipath routing protocol which used in this research. Multipath routing protocols can determine several routes between source nodes and destination nodes, this will provide benefits in terms of performance such as increased performance on network reliability. Beside routing protocol, a mobility model is needed to maintain the movement of nodes. Gauss-Markov is a mobility model used in this research, where Gauss-Markov will maintain movement of nodes based on the speed and angle (alpha) of movement. This research discuss analysis Ad-hoc On Demand Multipath Distance Vector (AOMDV) routing protocol using the Gauss-Markov mobility model on Mobile Ad-hoc Network (MANET) using Network simulator 2. The results of the simulation are if the number of nodes and the area of the simulation are increasing the value of end to end delay and normalized routing overhead will be increased, while the value of throughput tends to be decreased.